Heterogeneous group decision making with thermodynamical parameters. Issue 1 (31st December 2022) - Ren, Peijia; Xu, Zeshui; Verma, Mohit; Zeng, Xiao-Jun; Liao, Huchang; Wang, Xinxin
Abstract: There often exist different types of information due to the subjective and objective criteria in practical decision-making problems, thus it is necessary to develop some efficient frameworks to deal with the decision-making problems with heterogeneous information. The paper proposes a framework for group decision-making problems with heterogeneous information with thermodynamical parameters consisting of three parts to achieving this goal. The first part builds the rectifications of criteria weights according to decision makers' confidence in evaluations. The second part adopts thermodynamical parameters to measure the numerical values and the data distribution of heterogeneous information to characterize the heterogeneous information fully. The last part applies the TODIM (an acronym in Portuguese for Interactive and Multicriteria Decision Making) to aggregate the decision-making results based on the characterized heterogeneous information without transforming it into a unified form. By depicting decision makers' different sensitive attitudes towards uncertainty by several mathematical expressions, experiments are performed to assess the sensitive attitudes' impacts on decision-making results with the proposed framework. Finally, a case study on the selection of a green supplier under the low-carbon economy is provided to illustrate the flexibility and feasibility of the proposed framework.